Conditioned Medium of IGF1-Induced Human Wharton’s Jelly Mesenchymal Stem Cells Effects on Sox9 Gene Expression and Level of COL2 and IL1β in Osteoarthritic Chondrocytes - Widowati, Wahyu; Kusuma, Hanna Sari Widya; Azis, Rizal; Eltania, The Fransiska; Nindya, Faradhina Salfa (Directorate for Research and Community Services (LPPM) ITB, 2024)
Wharton’s jelly mesenchymal stem cells (WJMSCs) hold promises for treating osteoarthritis (OA) due to their great capacity for regeneration and their accessibility. However, obstacles like poor cell survival and differentiation prevent them from being used in transplants. Thus, this study examined WJMSCs’ Conditioned Medium (CM) (WJMSCs-CM) for OA treatment. In order to determine how well IL1β-induced chondrocyte cells (IL1β-CHON002) heal OA-damaged cells, they were treated with both IGF1-induced and uninduced WJMSCs-CM. Key parameters measured were IL1β, Sox9 and COL2. The STRING database was explored to evaluate the proteins contained in WJMSCs-CM and to see their interactions and CM potential in OA exposure. The STRING database indicates WJMSCs-CM to possess the ability to manage OA because of the growth factors they contain, which raise the expression of cartilage marker genes. The results indicated that 15% WJMSCs-CM with 150 ng/mL IGF1 had the highest Sox9 expression, significant reduction in pro-inflammatory mediators, and an increase in COL2 levels. Additionally, 14 days of treatment resulted in better outcomes compared to 7 days. CM from WJMSCs treated with IGF1 with a concentration of 15% exhibited the highest level for each parameter. Both durations showed difference across parameters, highlighting the potential for OA therapy.